Oral Administration of Shark Type II Collagen Suppresses Complete Freund's Adjuvant-Induced Rheumatoid Arthritis in Rats - Wenhui Wu; Jing Xie; Nanping Wang; Bin Bao; Lijuan Chen (MDPI AG, 2012)
Objective: Shark type II collagen (SCII) is extracted as a glycoprotein from the cartilage of blue shark (Prionace glauca). We aim to confirm the effects of oral tolerance of SCII on inflammatory and immune responses to the ankle joint of rheumatoid-arthritis rats induced by Complete Freund's Adjuvant (CFA). Materials and Methods: The onset of rheumatoid arthritis (RA) was observed 14 ± x days after injection of CFA. Rats in the control group were treated with acetic acid by oral administration (0.05 mmol kg−1d−1, days 14-28), while rats in experimental groups were treated by oral administration with SCII (1 or 3 mg kg−1d−1, days 14-28), Tripterygium wilfordii polyglycosidium (TWP) (10 mg kg−1d−1, days 14-28), and bovine type II collagen from US (US-CII) (1 mg kg−1d−1, days 14-28), respectively. The severity of arthritis was evaluated by the articular swelling. The immunological indexes observed included delayed type hypersensitivity (DTH) reaction, the level of interleukins 10 (IL-10) in rat blood serum and morphological characterization. Mixed lymphocyte culture (MLC) was performed to investigate the relationship between T cell apoptosis and specific immune tolerance induced by SCII. Results: Treatment with SCII for 2 weeks significantly attenuated the acute inflammation. The rats orally administrated with SCII at the level of 3 mg kg−1d−1 (SCII 3) and US-CII had decreased DTH reaction compared with rats in control group. Rats treated with SCII 3 had the highest level of IL-10 with 102 pg/mL. SCII with concentration of 10 μg/L could help to significantly enhance level of Fas/Apo-1 in T cell in vitro. The result of histological staining indicated that the recovery of the articular membranes of ankle joint in SCII 3 group was greatly enhanced. Conclusions: Our results suggest that appropriate dose of SCII can not only ameliorate symptoms but also modify the disease process of Complete-Freunds-Adjuvant-induced arthritis. Oral administration of SCII might be a potential candidate as a novel drug for further investigation.